The effects of a home telerehabilitation-based program on the cardiopulmonary function and quality of life in post-COVID-19 patients - Thanaporn Semphuet; Netchanok Jianramas; Veeranoot Nissapatorn; Chaisith Sivakorn; Maria De Lourdes Pereira; Anuttra (Chaovavanich) Ratnarathon; Chenpak Salesingh; Eittipad Jaiyen; Salinee Chaiyakul; Nitita Piya-Amornphan; Thanrada Thiangtham; Khomkrip Longlalerng (Heliyon)
Background: Relatively few studies have explored the impact of home telerehabilitation-based (HTB) programs on patients with post-COVID-19 syndrome. Thus, this study aimed to investigate the effect of HTB programs on the cardiopulmonary function, body composition, muscle strength, and quality of life (QoL) of patients with post-COVID-19 syndrome. Methods: A quasi-experimental study was performed. Fifty-one patients with COVID-19 were divided into two groups after being discharged from the hospital. Participants in the control group (n = 26) were advised to engage in breathing and stretching exercises plus their preferred exercise program. In comparison, participants in the intervention group (n = 25) were instructed to perform a combination of aerobic, breathing, and resistance exercises. To monitor the exercise program at home, the physiotherapists called the participants using a mobile phone application platform once a month and once a week in the control and intervention groups, respectively. Outcome measurements consisted of cardiopulmonary functions including exercise capacity using the 6-min walk test (6 MWT), and the pulmonary function test (PFT). Leg muscle strength and endurance were determined using the 1-min sit-to-stand test (1MSTS). Other physical fitness parameters were also examined including the hand grip strength test and body composition attributes. The 36-item Short Form questionnaire was used to determine the quality of life. All outcome measurements were tested before hospital discharge and at 3-month follow-up. Results: Participants of the control (n = 18) and intervention (n = 14) groups completed a 3-month post-discharge exercise program. No statistically significant differences were found between the two groups for all outcome measurements (p > 0.05). However, the 6 MWT and 1MSTS values increased significantly at the time of the 3-month follow-up compared to the baseline values at the time of discharge for both groups. Conclusion: Patients with post-COVID-19 syndrome exhibited beneficial effects on exercise capacity, leg muscle strength, and endurance after completing a 3-month duration post-discharge HTB program. Trial registration: https://thaiclinicaltrials.org/ with identifier number TCTR20210823004.